Diagnostic Problems in Leptospirosis Patients : A Case Report - Megawati; Musofa Rusli (Institute of Medico-legal Publications Pvt Ltd, 2022)
Leptospirosis is a zoonosis infection found in almost every part of the world but is mostly endemic in tropical and subtropical countries. In 2013 there were 640 new cases reported with 60 death cases (CFR 9.37%). An increase in new cases had caused an outbreak in Sampang, Madura due to a flood following a high rainfall. A male patient aged 45 years old with Leptospirosis. The diagnosis was made based on the epidemiology, clinical manifestations, and Microscopic Agglutination Test (MAT) examination data. In the early treatment, the examination of IgM and IgG Leptospira showed negative results a confirmation with MAT examination was done subsequently. Diagnosis using MAT also provides information about an outbreak in a region. Upon receiving antibiotic and symptomatic treatments and clinical recovery, the patient’s condition continued to improve.